Stock price forecasting for Jordan insurance companies amid the COVID-19 pandemic utilizing off-the-shelf technical analysis methods - Ghada A. Altarawneh; Ahmad B. Hassanat; Ahmad S. Tarawneh; Ahmad Abadleh; Malek Alrashidi; Mansoor Alghamdi (Economies, 2022)
One of the most difficult problems analysts and decision-makers may face is how to improve the forecasting and predicting of financial time series. However, several efforts were made to develop more accurate and reliable forecasting methods. The main purpose of this study is to use technical analysis methods to forecast Jordanian insurance companies and accordingly examine their performance during the COVID-19 pandemic. Several experiments were conducted on the daily stock prices of ten insurance companies, collected by the Amman Stock Exchange, to evaluate the selected technical analysis methods. The experimental results show that the non-parametric Exponential Decay Weighted Average (EDWA) has higher forecasting capabilities than some of the more popular forecasting strategies, such as Simple Moving Average, Weighted Moving Average, and Exponential Smoothing. As a result, we show that using EDWA to forecast the share price of insurance companies in Jordan is good practice. From a technical analysis perspective, our research also shows that the pandemic had different effects on different Jordanian insurance companies.
Keywords: 330; financial time series forecasting; forecasting methods; stock markets; technical analysis